Using the principles of «Just-In-Time» model in long-distance road transport organizing - Нефьодов, Віктор Миколайович; Сажко, М. В. (Eastern-European Journal of Enterprise Technologies, 2009)
Deadlines of orders on the effectiveness of transportation of mineral fertilizers in intercity are considered. The dependencies can be used in the planning of cargo in intercity rolling stock with the arrival to the consignee just in time are considered in the article